IMPACT OF SHORT-TERM EXERCISE TRAINING ON ARTERIAL BLOOD PRESSURE AND QT DISPERSION IN DIABETIC PATIENTS AFTER MYOCARDIAL INFARCTION. (June 2018) - Stoickov, V.; Ilic, M. Deljanin; StoickoV, M.; Saric, S.; Simonovic, D.; Marinkovic, D.; Stoickov, I.; Andonov, S.; Mitic, S.
Abstract : Objective: The aim of this study was to establish the influence of short-term exercise training on arterial blood pressure and QT dispersion in diabetic patients after myocardial infarction. Design and method: The study involved 139 diabetic patients after myocardial infarction (average age 55.7 years), in the sinus rhythm without AV blocks or branch blocks. Patients were randomly divided into the physical training group (TG: 115 patients) and non-training group (NTG: 24 patients). Patients were of similar age, site of infarction and baseline stress test duration. In all subjects standard ECG and exercise test on treadmill were performed and after that TG patients were included in a training program for three weeks. TG patients were instructed to follow a training program using the bicycle ergometer (10 min, 2 times a day), gymnastic exercises, and walking. The patients continued to take the same medicaments in same doses. From standard ECG corrected QT dispersion (QTdc) was calculated. Results: After program of physical training in TG of patients, significant reduction of QTdc was found, from 81.9 ± 24.8 to 73.5 ± 23.7 ms; p < 0.01. Also, in TG of patients, after program of physical training, we have found significant reduction of systolic blood pressure from 137.6 ± 12.9 to 128.4 ± 12.1 mmHg; p < 0.001; of diastolic blood pressure from 87.1 ± 7.9 to 82.9 ± 9.1 mmHg; p < 0.001 and of double product from 12834.6 ± 1975.2 to 11392.1 ± 1684.3 beat/min x mmHg; p < 0.001. In TG of patients, after program of physical training, significant reduction of glycemia was found, from 7.9 ± 2.9 to 6.9 ± 1.9 mmol/L; p < 0.005. In contrast, NTG of patients showed no significant changes. Conclusions: Short-term exercise training has favourable effects on arterial blood pressure and QT dispersion in diabetic patients after myocardial infarction. Physical training led to the significant decrease of myocardial oxygen uptake at rest and probably decreased the possibility of arrhythmia events in diabetic patients after myocardial infarction.